RISK FACTORS FOR DEVELOPING ATOPIC DISEASES AND MODERN DIAGNOSTICS METHODS - M.A. Snovskaya; O.V. Kozhevnikova; A.K. Gevorkyan; R.М. Torshkhoeva; L.S. Namazova-Baranova (Union of pediatricians of Russia, 2010)
The article is devoted to the 29th Congress of the European Academy of Allergy and Clinical Immunology (EAACI-2010) held in the June of 2010 in London. The authors cover in great detail the actual issues related to the prevention, diagnostics and treatment of atopic diseases. The article provides results of research and experiments. It outlines the current views on pre- and postnatal risk factors for developing allergies. It also illustrates the latest data on allergy diagnostics and capabilities of microchips. Key words: allergology, clinical immunology, congress, children. (Pediatric Pharmacology. - 2010; 7(5):99-103)